A Herd Investigation Tool in Support of the Irish Bovine Viral Diarrhoea Eradication Programme - Guelbenzu-Gonzalo, Maria P.; Lozano, Jose-Maria; O'Sullivan, Padraig; Lane, Elizabeth A.; Graham, David A. (Frontiers in Veterinary Science, 2021)
Bovine viral diarrhoea (BVD) is an important endemic disease of cattle. In Ireland, an industry-led compulsory eradication programme began in January 2013. The main elements of this programme are the identification and elimination of persistently infected (PI) calves by testing all new-borns, the implementation of biosecurity to prevent re-introduction of disease and continuous surveillance. In 2016, a standardised framework was developed to investigate herds with positive results. This is delivered by trained private veterinary practitioners (PVP). The investigation's aims are 3-fold: firstly, to identify plausible sources of infection; secondly, to ensure that no virus-positive animals remain on farm by resolving the BVD status of all animals in the herd; and thirdly, agreeing up to three biosecurity measures with the herd owner to prevent the re-introduction of the virus. Each investigation follows a common approach comprising four steps based on information from the programme database and collected on-farm: firstly, identifying the time period when each virus-positive calf was exposed in utero (window of susceptibility, taken as 30–120 days of gestation); secondly, determining the location of the dam of each positive calf during this period; thirdly, to investigate potential sources of exposure, either within the herd or external to it; and finally, based on the findings, the PVP and herdowner agree to implement up to three biosecurity measures to minimise the risk of reintroduction. Between 2016 and 2020, 4,105 investigations were completed. The biosecurity recommendations issued more frequently related to the risks of introduction of virus associated with contact with neighbouring cattle at pasture, personnel (including the farmer), the purchase of cattle and vaccination. Although each investigation generates farm-specific outcomes and advice, the aggregated results also provide an insight into the most commonly identified transmission pathways for these herds which inform overall programme communications on biosecurity. The most widely identified plausible sources of infection over these years included retained BVD-positive animals, Trojan births, contact at boundaries and indirect contact through herd owner and other personnel in the absence of appropriate hygiene measures. While generated in the context of BVD herd investigations, the findings also provide an insight into biosecurity practises more generally on Irish farms.